Detecting WIMPs, neutrinos and axions in the next generation of dark matter experiment - O'Hare, Ciaran A. J. (2017)
The first direct detection of dark matter is anticipated in coming years by one of a range of experimental strategies. Because the identity of dark matter remains unknown, the strategy that will be successful in this one cannot say. However beneath this fundamental particle physics uncertainty lies another uncertainty with regard to the structure of the dark matter halo of the Milky Way that must be confronted when interpreting data from terrestrial experiments. However these astrophysical uncertainties might only be resolved with the very same experiments; in fact, directly detecting dark matter represents the only way to probe the ultralocal structure of the halo. This thesis explores the impact of astrophysical uncertainties on the particle physics goals of dark matter detection but also the extent to which we might in the future be able to resolve those uncertainties. The discussion is framed around the detection of three types of particle, two of which are dark matter candidates: weakly interacting massive particles (WIMPs), neutrinos and axions.